Bone regeneration in a rabbit critical femoral defect by means of magnetic hydroxyapatite macroporous scaffolds. Issue 2 (15th February 2017) - Russo, A.; Bianchi, M.; Sartori, M.; Boi, M.; Giavaresi, G.; Salter, D. M.; Jelic, M.; Maltarello, M. C.; Ortolani, A.; Sprio, S.; Fini, M.; Tampieri, A.; et al.
Abstract: Magnetic scaffolds have recently attracted significant attention in tissue engineering due to the prospect of improving bone tissue formation by conveying soluble factors such as growth factors, hormones, and polypeptides directly to the site of implantation, as well as to the possibility of improving implant fixation and stability. The objective of this study was to compare bone tissue formation in a preclinical rabbit model of critical femoral defect treated either with a hydroxyapatite (HA)/magnetite (90/10 wt %) or pure HA porous scaffolds at 4 and 12 weeks after implantation. The biocompatibility and osteogenic activity of the novel magnetic constructs was assessed with analysis of the amount of newly formed bone tissue and its nanomechanical properties. The osteoconductive properties of the pure HA were confirmed. The HA/magnetite scaffold was able to induce and support bone tissue formation at both experimental time points without adverse tissue reactions. Biomechanically, similar properties were obtained from nanoindentation analysis of bone formed following implantation of magnetic and control scaffolds. The results indicate that the osteoconductive properties of an HA scaffold are maintained following inclusion of a magnetic component. These provide a basis for future studies investigating the potential benefit in tissue engineering of applying magnetic stimuli to enhance bone formation. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 546–554, 2018.